Unlocking Scientific Knowledge with Statistical Tools in JMP® : Benefits and challenges of new statistical tools. Issue 2 (5th April 2022) - Jiménez, Pilar Gómez; Fish, Andrew; Bosch, Cristina Estruch
The value of using statistical tools in the scientific world is not new, although the application of statistics to disciplines such as chemistry creates multiple challenges that are identified and addressed in this article. The benefits, explained here with real examples, far outweigh any short-term barriers in the initial application, overall saving resources and obtaining better products and solutions for customers and the world. The accessibility of data in current times combined with user-friendly statistical packages, such as JMP®, makes statistics available for everyone. The aim of this article is to motivate and enable both scientists and engineers (referred to subsequently in this article as scientists) to apply these techniques within their projects.